Adverse events of non-ablative fractional laser photothermolysis: a retrospective study of 856 treatments in 362 patients. (August 2013) - Lee, Sang Min; Kim, Myoung Shin; Kim, Youn Jin; Won, Chong Hyun; Lee, Mi Woo; Choi, Jee Ho; Moon, Kee Chan; Chang, Sung Eun
Background: Non-ablative fractional laser photothermolysis (NAFP) has been used effectively in the treatment of photodamaged skin and scars, with short post-operative recovery times; but, studies evaluating its adverse events and complication rates in Asian population have been limited. Objective: To determine the frequency and range of adverse events associated with NAFP treatment in Korean patients. Materials and methods: We retrospectively evaluated the outcomes of 754 1550-nm erbium-doped and 102 1927-nm thulium fiber fractional laser treatments in patients with skin phototypes III–IV treated at a single center. Adverse events were identified and tabulated, as were patient demographics and laser parameters. Results: From 856 treatments, there were 43 adverse events (5.0%), the most frequent being prolonged erythema (1.8%), post-inflammatory hyperpigmentation (1.1%) and aggravation of melasma (0.9%). Less frequently observed adverse events included herpes simplex outbreak (0.6%) and acneiform eruption (0.2%). There were no reports of long-term adverse events. Conclusion: Non-ablative fractional laser skin treatment has a relatively low complication rate. The adverse events found were temporary and did not result in long-term or severe sequelae such as hypertrophic scarring, atrophic scarring or permanent pigmentary alteration.